PENGARUH PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI ERA REVOLUSI INDUSTRI 4.0 - Berlina Titania Anggraenie; Diana Hanafiah; Yustrisya Ni’mahtus Sa’diah (PROCEEDING UMSURABAYA, 2022)
Islamic religious education is an important lesson in the development of student character. The existence of character education in schools is very necessary and useful for all kids at school because character education will teach students how to endure, avoid things that are not allowed and are absolutely not good, and become better humans. It is critical for schools to teach children through generating educational discoveries in order to maximize character development in them. This is inextricably linked to the issues of technology advancement and globalization, which easily persuade children to make social detours. The purpose of this study is to discover how Islamic religious education is implemented in schools, as well as the impact of learning Islamic belief education on the character of children at school and in everyday life. The descriptive strategy was employed in the qualitative research method. This study's subjects were elementary school students. What will happen is that the research explains that Islamic belief education is in creating the character of pupils who can think, behave, behave on demand, inculcate character values in order to produce direct reliable and consistent usage of its principles through the educational process Keywords: Learning, Islamic Religious Education, Character Education For Elementary School